The Validity and Reliability of the Marmara Learning Styles Scale (MLSS) - (:unkn) unknown (EDAM, 2007)
The science of education has focused on alternative educational approaches for years with a view to meeting the needs of wide student audiences in classes. One of the sources of the differences in learning performance at class environment is the learning styles. This study has been conducted to develop it learning styles scale for students at the secondary education level. Within the scope of the study, a learning styles scale for the secondary education level tailored to the conditions in Turkey has also been developed. The study wits started with 223 items and implementations were carried out on 909 high school students. After the study, Cronbach's Alpha coefficient was determined as 0.95. Furthermore, it was determined that item-total and corrected item-total correlations were significant and items were discriminative, The factor analysis has yielded that the items group tinder a total of 8 factors, total variance amount described was around 0.56 and that significant correlations were present between the factors.
Keywords: Learning; Learning Styles; Cognitive Learning; Secondary Education